Comparative pharmacokinetics of seven bioactive components after oral administration of crude and processed Qixue Shuangbu Prescription in chronic heart failure rats by microdialysis combined with UPLC-MS/MS. (1st March 2023) - Chen, Linwei; Wei, Nina; Jiang, Yong; Yuan, Chengye; Xu, Luwei; Li, Jindong; Kong, Min; Chen, Yan; Wang, Qin
Abstract: Ethnopharmacological relevance: Qixue Shuangbu Prescription (QSP) is a classical traditional Chinese medicine prescription, which has widely used for the treatment of chronic heart failure (CHF). Preliminary clinical studies have shown that the efficacy of processed QSP (P-QSP) in treating CHF is greater than crude QSP (C-QSP). However, the pharmacokinetic characteristics of its major bioactive components under pathological conditions are unclear. Aim of study: This study aims to compare pharmacokinetics of seven bioactive components after oral administration of C-QSP and P-QSP in CHF model rats. Materials and methods: Ginsenoside Rb1, ginsenoside Re, ginsenoside Rg1, ferulic acid, astragaloside IV, calycosin-7-O-β-D-glucoside, and paeoniflorin in QSP were used as the target components. CHF model in rats was induced by the intraperitoneal injection of doxorubicin. A microdialysis combined with UPLC-MS/MS method was first established to compare the pharmacokinetics of seven major bioactive components in CHF model rats after oral administration of C-QSP and P-QSP. Results: This method was successfully applied to the pharmacokinetic investigation of seven major components of C-QSP and P-QSP following oral administration in CHF model rats. Compared with the C-QSP group, the Cmax, AUC0-t and AUC0−∞ of ginsenoside Rb1, ginsenoside Re, ginsenoside Rg1, ferulic acid, astragaloside IV and paeoniflorin significantly increased ( P  < 0.05) in the P-QSP group, which suggested that the absorptivity and bioavailability were increased. Lower T1/2, MRT0−t of ginsenoside Rb1, gerulic acid and higher T1/2, MRT0−t of ginsenoside Rb1, astragaloside IV, paeoniflorin in the P-QSP group, which indicated that eliminated more quickly or slowly, respectively. Conclusions: The pharmacokinetic parameters of bioactive components were significantly changed for better bioavailability and absorption, longer lasting time elimination, which were beneficial for enhancing therapeutic efficacy in the P-QSP group. This study will provide a new perspective to explain the pharmacokinetic-pharmacodynamic correlation of P-QSP on the treatment of CHF. Graphical abstract: Image 1 Highlights: A microdialysis combined with UPLC-MS/MS method was applied to study the pharmacokinetic characteristics of QSP. The pharmacokinetic profiles of seven bioactive components after oral administration of QSP in CHF model rats. Pharmacokinetic parameters would provide data support for the clinical application of processed QSP.